Peran Preferensi Konsumen Anime Genre Isekai Terhadap Generasi Z - Fadhilah, Muhammad Rafi; Ramadhini, Yulanda Rizqi; Lestari, Humannisa Rubina; Raifa, Malvian Fikra; Fadhilah, Dany; Kusnadi, Khairunnisa Hayyu; Shafaresta, Nadhila; Yusuf, Ihzra Fahrullizian (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2025)
This research investigates the influence of consumer preferences for the Isekai anime genre among Generation Z in Indonesia. As a prominent element of Japanese popular culture, anime has achieved global popularity, particularly among young people, including those in Indonesia. The Isekai genre, known for its alternate world settings, engaging plots, and intricate characters, stands out as a top favorite. Utilizing a qualitative methodology, this study examines the factors that shape Generation Z's affinity for the Isekai genre and its connection to their demographic profiles. Data collection involved in-depth interviews and surveys with Generation Z individuals who are enthusiasts of Isekai anime. The results indicate that Generation Z is primarily drawn to the Isekai genre due to its unique narratives and otherworldly settings, along with its nuanced characters. Furthermore, their preferences are shaped by the convenience of streaming platforms, active fan networks, and the impact of social media. The study also highlights that a preference for Isekai anime significantly affects the attitudes and cultural consumption behaviors of Generation Z. This research offers critical insights for the anime industry to better engage and understand the Generation Z demographic. Additionally, it sheds light on how the Isekai anime genre can shape individual development within the realm of popular culture. By understanding Generation Z's preferences and the factors influencing them, anime creators can develop more targeted strategies to boost audience engagement and loyalty.